2015
DOI: 10.3892/or.2015.4110
|View full text |Cite
|
Sign up to set email alerts
|

CD44 alternative splicing and hnRNP A1 expression are associated with the metastasis of breast cancer

Abstract: Abstract. CD44 is a transmembrane receptor for hyaluronic acid. CD44 pre-mRNA contains 19 exons, 9 of which are alternatively spliced. Among the CD44 spliced variants, the v4-7 variant, one of the v6 exon-containing isoforms that contains variable exon 4, 5, 6 and 7, confers metastatic potential to nonmetastatic cells. Splicing of CD44 and the function of CD44 isoforms are different in breast cancer cells. hnRNP A1 is a ubiquitously expressed protein with an inhibitory function in pre-mRNA splicing. We showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 31 publications
0
53
0
1
Order By: Relevance
“…Moreover, it is well known that hnRNPs play a critical role in pre‐mRNA splicing and hnRNPA, L, and M 11 may regulate splicing of CD44 variants. CD44 alternative splicing is differentially regulated by hnRNPM during EMT, resulting in a switch in expression from the variable exon‐containing CD44v isoforms to the standard isoform, CD44s.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it is well known that hnRNPs play a critical role in pre‐mRNA splicing and hnRNPA, L, and M 11 may regulate splicing of CD44 variants. CD44 alternative splicing is differentially regulated by hnRNPM during EMT, resulting in a switch in expression from the variable exon‐containing CD44v isoforms to the standard isoform, CD44s.…”
Section: Introductionmentioning
confidence: 99%
“…The existence of these different isoforms increases the heterogeneity of the CD44 protein products and there are discrepancies in the literature about the roles of CD44v and CD44s in tumor progression. [17][18][19] Moreover, it is well known that hnRNPs play a critical role in pre-mRNA splicing and hnRNPA, [20][21][22] L, and M 11 may regulate splicing of CD44 variants. CD44 alternative splicing is differentially regulated by hnRNPM during EMT, resulting in a switch in expression from the variable exon-containing CD44v isoforms to the standard isoform, CD44s.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have indicated that .95% of human genes undergo alternative splicing and that many point mutations that result in human genetic disease have disrupted splicing (38,39). Moreover, many immunologically relevant genes have been observed to undergo alternative splicing (40)(41)(42)(43). The present study includes four major findings.…”
Section: Discussionmentioning
confidence: 69%
“…(23) Among these variants, the expression of CD44v6-10 is much higher than other variants in MCF7 cells. (24) Semiquantitative PCR showed that, among these variants, the expression of CD44s and CD44v mRNA was increased by SAC1 knockdown in MCF7 ( Fig. 1b) and SK-BR-3, another luminal-type, HER-2-enriched breast cancer cell (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Although MCF7 cells predominantly express CD44s, CD44 variants, including CD44v6‐10, v2‐10, and v3‐10, are also expressed . Among these variants, the expression of CD44v6‐10 is much higher than other variants in MCF7 cells . Semiquantitative PCR showed that, among these variants, the expression of CD44s and CD44v mRNA was increased by SAC1 knockdown in MCF7 (Fig.…”
Section: Resultsmentioning
confidence: 99%